(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Video indexing, intelligent surveillance, multimedia understanding, and other domains all make extensive use of video action recognition. Lately, it was significantly enhanced by adding deep learning through Convolutional Neural Network (CNN) learning. This inspired us to examine the noteworthy efforts on action recognition using CNN. This paper presents a clear and objective overview of CNN-based action recognition and offers recommendations for further research.